2010
DOI: 10.1016/j.jcv.2010.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Flower cells in patients with infective dermatitis associated with HTLV-1

Abstract: This is the first report on the presence of flower cells in HTLV-1-infected children and adolescents. Furthermore, these cells have not previously been reported in IDH patients. The cases with flower cells probably represent precursory ATL cases, these patients being at a greater risk of developing ATL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…IDH patients typically have a high HTLV-1 proviral load, comparable to HAM/TSP patients [26]. IDH is suspected to increase the risk of HAM/TSP or ATLL development [26], [27], [28], [29], but the evidence is not conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…IDH patients typically have a high HTLV-1 proviral load, comparable to HAM/TSP patients [26]. IDH is suspected to increase the risk of HAM/TSP or ATLL development [26], [27], [28], [29], but the evidence is not conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Human T-cell leukemia virus type I (HTLV-I) was the first retrovirus identified in humans, isolated from a patient with cutaneous lymphoma (Poiesz et al 1980 ). HTLV-I is the cause of not only adult T-cell leukemia/lymphoma (ATL) (Uchiyama et al 1977 ; Hinuma et al 1981 ) but also HTLV-I-associated myelopathy (HAM)/tropical spastic paraparesis (TSP) (Osame et al 1986 ), HTLV-I-associated uveitis (HU) (Ohba et al 1989 ; Mochizuki et al 1992 ) and infective dermatitis (McGill et al 2012 ; de Oliveira et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, four cases of ID were found, such as Okajima et al ., who found three cases of ID in their work, however, other studies have not reported patients with this diagnosis . It should be considered that patients from this and the other cited studies were predominantly adults and although cases of ID have been reported in adults, the disease is rare and is considered a form of childhood dermatitis …”
Section: Discussionmentioning
confidence: 45%
“…However, cases of ID have been reported in adults as well. It is presented as an exudative eruption involving mainly seborrheic areas such as: scalp, forehead, eyelids, paranasal sinuses, external ear, periauricular region, neck, armpits, and inguinal region . Differential diagnosis should be made with atopic dermatitis and seborrheic dermatitis …”
Section: Introductionmentioning
confidence: 99%